Successful Treatment of Sjögren’s Syndrome Presenting as a Condition Similar to Chronic Capillary Leak Syndrome Using Combination Therapy with High-Dose Intravenous Immunoglobulin and Glucocorticoid - Masami Tokura; Tomoko Niwano; Kenji Nagasaka (Case Reports in Rheumatology)
A 70-year-old woman with Sjögren’s syndrome (SS) complained of generalized edema. Computed tomography showed thoracoabdominal fluid, suggesting serositis with SS. 35 mg/day of prednisolone as a monotherapy was ineffective. Moreover, hemoconcentration with hypoalbuminemia without inflammatory signs lead us to consider the systemic capillary leak syndrome (SCLS). Additional treatment with intravenous immunoglobulin (IVIG) and prednisolone dramatically decreased the thoracoabdominal fluid. However, when reducing the prednisolone dose, the thoracoabdominal fluid reincreased. Retreatment with IVIG without increasing the prednisolone dose was ineffective. However, additional prednisolone of 35 mg/day was effective, suggesting SCLS with SS might require combination therapy with IVIG and glucocorticoid.